High-quality dialysis: a lesson from the Japanese experience: Effects of membrane material on nutritional status and dialysis-related symptoms - Masakane, Ikuto (NDT Plus, 2010)
High-quality dialysis does not always mean high efficiency; dialysis should maintain nutritional balance and full biocompatibility. In undergoing treatment with polymethylmethacrylate (PMMA) and/or ethylene vinyl alcohol copolymer (EVAL) membrane dialysers, the body weight decrease caused by polysulfone membrane has been dramatically improved for those receiving predilution online haemodiafiltration (HDF) as well. These membranes are assumed to somewhat suppress the clearance of small molecular weight substances to maintain an exquisite balance of broadly removing low molecular weight proteins. This removal process is assumed to be extremely close to the balance maintained by the clearing characteristics of the kidneys. On the other hand, fluid purification is also one of the important factors in high-quality dialysis. Bacteriological contamination of dialysis fluid is one of the serious factors that deteriorate the biocompatibility of dialysis therapy. From this therapeutic concept, the patient survival rate is excellent in our facilities: the 1-year survival rate is 91.1% and the 5-year survival rate is 76.6%, although the mean age of our patients is 69 years. We usually adjust the therapeutic modality based on patient complaints, and we call this concept ‘patient-oriented dialysis’ (POD). In the POD system, the prevalence of uraemic pruritus or sleep disturbances was lower than that of the DOPPS. The protein-leaking dialysis modalities with PMMA, EVAL or predilution online HDF form the key concept in the POD system.